PERCEPTIONS AND COMPETENCY READINESS OF ACCOUNTING STUDENTS IN EMBRACING DIGITAL FINANCIAL ACCOUNTING: A MIXED METHODS CASE STUDY - Ismail, Juniaty; Noholo, Sahmin; Abdullah, Fony (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. The advancement of digital technology has transformed accounting practices from manual systems to digital platforms such as software, cloud computing, and artificial intelligence. This shift requires accounting students to master both conceptual knowledge and digital competence in line with current industry needs. Research Purpose. This study aims to describe accounting students’ perceptions of digital financial accounting implementation and examine their competency readiness, particularly within the local context of Gorontalo, a region underrepresented in accounting education research. Research Method. A mixed-methods case study design was employed, involving 13 higher education accounting students as respondents. Quantitative data were collected through a questionnaire based on the constructs of the Technology Acceptance Model (TAM), the Technology Readiness Index (TRI), and the Unified Theory of Acceptance and Use of Technology (UTAUT), combined with digital competency indicators. Descriptive statistics calculated the mean, median, and standard deviation, while qualitative data from essay responses were analyzed thematically to identify key patterns. Findings. Most students perceive digital accounting as beneficial in improving learning efficiency (mean = 4.07). However, aspects of digital competence, including content creation and data security, remain moderate (mean = 3.0–3.3). Essay responses indicate optimism, hands-on practice, and data protection issues. Conclusion. An initial understanding of accounting students’ perceptions and readiness for digital transformation in Eastern Indonesia serves as a foundation for developing accounting curricula emphasizing digital competence and practical application.